Analisis Struktur dan Fungsi Bahasa Suku Hubula Lembah Balim Papua dalam Perkembangan Era Moderen: Analysis of The Structure and Function of Hubula Language From Balim Valley Papua in The Development of Modern Era - Grets Lewis Theodore Walilo (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
The purpose of this study is to understand the structure and function of Hubula tribe language from Balim Valley Papua with its development in the modern era. Whereas, the language has an easy sentence pattern to be identified. This research was conducted with a sociolinguistic approach that focused on the usage of language in the society to perform its function. The result showed that Hubula tribe language is still favorable in Balim Valley even at the modern era. By knowing some basic vocabularies, the sentence’s structure of Hubula tribe language can be identified easily. As the bridge for interaction, this language has several functions such as; personal function, informative function, interaction function and regulatory function.